STUDY OF NEEDS AND AVAILABILITY OF CLEAN WATER PALANGKA RAYA CITY - Airways Parlindungan Siahaan (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2019)
Palangka Raya City, one of the candidates for Indonesia's capital city, has made Palangka Raya develop very rapidly. The development of the City encourages an increase in population. Therefore, planning for clean water needs for Palangka Raya City is needed. Calculation of projected population growth using the Least Square Method. Calculation of domestic clean water needs and non-domestic water needs using the standards of the Directorate General of Human Settlements. In addition to calculating the need for clean water, calculating the availability of water until 2037. Water quality distribution of PDAM Palangka Raya City has met the requirements for class B standards, namely water that can be used as raw material for drinking water. PDAM Kota Palangka Raya has an existing intake of 200 liters / second, according to projection calculations using the linear regression method it is found that the need for clean water by 2037 is 1060.2 liters / second and the availability of water is 2877 liters / second until 2037, it can be said to in 2037 the need for clean water is fulfilled.